Want this question answered?
Be notified when an answer is posted
6x plus 3y minus 2x plus 5y equals 4x plus 8y.
The question is not quite clear, do you mean -6x+3y = -18 and -10+5y = -30? If so then the solution is: -10+5y= -30 5y = -30+10 5y = -20 y = -4 Substitute the value of y into the equation -6x+3y = -18: Answer: x = 1 and y = -4
It is: 6x-5y simplified
86
3x-3y
6x-3y
(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)
6x plus 3y minus 2x plus 5y equals 4x plus 8y.
The LCM is 30xy.
4x-2y
The question is not quite clear, do you mean -6x+3y = -18 and -10+5y = -30? If so then the solution is: -10+5y= -30 5y = -30+10 5y = -20 y = -4 Substitute the value of y into the equation -6x+3y = -18: Answer: x = 1 and y = -4
It is: x-5y simplified
It is: 6x-5y simplified
86
3x-3y
It's an algebraic expression that can be simplified to: x-5y
3x+5y=48 5y=48-3x-3x+5y=12 -3x+(48-3x)=12-6x=-36x=65y=48-3(6)5y=30y=6(6,6)